2015
DOI: 10.1128/aem.02628-15
|View full text |Cite
|
Sign up to set email alerts
|

Facultative Control of Matrix Production Optimizes Competitive Fitness in Pseudomonas aeruginosa PA14 Biofilm Models

Abstract: cAs biofilms grow, resident cells inevitably face the challenge of resource limitation. In the opportunistic pathogen Pseudomonas aeruginosa PA14, electron acceptor availability affects matrix production and, as a result, biofilm morphogenesis. The secreted matrix polysaccharide Pel is required for pellicle formation and for colony wrinkling, two activities that promote access to O 2 . We examined the exploitability and evolvability of Pel production at the air-liquid interface (during pellicle formation) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 61 publications
(83 reference statements)
5
74
1
Order By: Relevance
“…EPS was measured in the quantitative Congo red (CR) binding assay, as previously described (28). Cultures were grown in BM2 with 20 M Mg 2ϩ containing a 10 M concentration of the reordered compounds in 5-ml glass tubes for 24 h at 37°C with shaking (150 rpm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPS was measured in the quantitative Congo red (CR) binding assay, as previously described (28). Cultures were grown in BM2 with 20 M Mg 2ϩ containing a 10 M concentration of the reordered compounds in 5-ml glass tubes for 24 h at 37°C with shaking (150 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were grown in BM2 with 20 M Mg 2ϩ containing a 10 M concentration of the reordered compounds in 5-ml glass tubes for 24 h at 37°C with shaking (150 rpm). For EPS quantification, CR was added at a final concentration of 40 g/ml to 2-ml cultures and bound dye was indirectly calculated by determination of remaining unbound dye still in solution (28).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental evolution studies provide evidence for the prediction that evolution in structured environments can favor adaptations to sociality (34,35,(42)(43)(44). For example, Koch and colleagues demonstrated how the emergence of a strain with an increased level of cell-cell communication can eventually lead to evolution of antibiotic resistance to vancomycin, a last-resort antibiotic (27).…”
mentioning
confidence: 99%
“…Lenski's experiment is still in progress, reaching 64,000 generations in January 2016, and many similar studies have been performed by other researchers on different microbial species (not only bacteria but also yeasts, phages, or protists) covering basic scientific questions (29,30) or even in directly applicative projects (31). While planktonic cultures offer a simple setup to study the evolution of bacteria (23,28,31,32), several studies have shown that the selective pressures in unstructured conditions differ from those in biofilms (33)(34)(35)(36). For example, homogeneous, well-mixed environments may select against "social" genotypes that secrete costly metabolites, so-called "public goods," and rather favor fast-reproducing selfish individuals (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation